A New Generation of Platinum‐Copper Electrocatalysts with Ultra‐Low Concentrations of Platinum for Oxygen‐Reduction Reactions in Alkaline Media. Issue 11 (19th March 2020) - Parkash, Anand; Jia, Zhou; Tian, Tang; Ge, Zhang; Yu, Chen; Chunli, Xu
Abstract: In order to reduce the cost and enhance the performance of the cathode catalyst for fuel cell, support‐less, ultra‐low Pt contents based nanostructured platinum copper (Pt−Cu) nanoparticles (NPs), with differential Pt‐contents, were prepared using CTAB‐reduction approach and avoiding utilization of high Pt contents, while keeping high electrocatalytic activity and durability. The novelty of present work lies in the suggested synthesis method for support‐free Pt−Cu NPs with lower Pt loadings (0.04‐0.25 wt.%). Pt0.25 Cu NPs (Eo 0.98 V vs. RHE) exhibits high ORR performance compared to Pt/C (20 wt.%) (Eo 0.97 V vs. RHE). The synthesis method of our Pt−Cu NPs will find wide application in the preparation of bimetallic nanocatalysts. Abstract : Herein, a low‐cost ORR catalyst with ultra‐low Pt content (0.04‐0.25%) was prepared by hydrothermal approach. Prepared novel catalyst Pt0.25 Cu NPs exhibits excellent electrocatalytic activity with a positive onset potential 0.98 V vs. RHE and half‐wave potential 0.84 V vs. RHE, which is superior compared to commercial Pt/C (20 wt.%) (Eo 0.97 V and E1/2 0.83 V vs. RHE). The durability is also superior than that of Pt/C.